Construction And Operation Of An Innovative Long Distance Conveying System At Twin Buttes - F. Brost (Society for Mining, Metallurgy & Exploration, 1979)
In 1976, a decision was made to install a conveying system to transport ore 10.3 km (6.4 miles) from the new Eisenhower Partnership Mine to Twin Buttes. The system, supplied and installed by Cable Belt Limited, of England, represents a radical departure from conventional conveyor systems. The driving tension is applied through two endless wire ropes while the belt acts only as the carrying medium. Features of the system are a single 2240 kw (3000 hp) drive and a 60° angle bend. Construction was completed in two years. Full production was attained after several months' operation.